Saponin-Induced Shifts in the Rumen Microbiome and Metabolome of Young Cattle - Wang, Bing; Ma, Man Peng; Diao, Qi Yu; Tu, Yan (Frontiers in Microbiology, 2019)
The aim of this study was to explore the effects of saponins on the rumen microbiota and the ruminal metabolome. Alfalfa hay (AH) and soybean hulls (SH) were used as fiber sources for the control diets. The AH and SH diets were supplemented with tea saponins resulting in two additional diets named AHS and SHS, respectively. These 4 diets were fed to 24 young male Holstein cattle (n = 6 per diet). After 28 days of feeding, the rumen fluid from these cattle was collected using an oral stomach tube. Illumina MiSeq sequencing and ultrahigh-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS) were used to investigate the changes in the ruminal microbes and their metabolites. The relative abundance of Prevotellaceae_YAB2003 increased, while Ruminococcaceae_NK4A214 and Lachnospiraceae_NK3A20 decreased in SHS and AHS compared to SH and AHS, respectively. Feeding SHS resulted in higher ruminal concentrations of squalene, lanosterol, 3-phenylpropanoic acid, and citrulline compared to SH. The different microbial genes predicted by Tax4Fun were involved in amino sugar and nucleotide sugar metabolism. The pathways of arginine and proline metabolism, purine metabolism, and pyrimidine metabolism were enriched by different metabolites. Moreover, in the SH group, a positive correlation was observed between Prevotella_1 (Bacteroidetes), Prevotellaceae_YAB2003 (Bacteroidetes), and Christensenellaceae_R.7 (Firmicutes), and the metabolites, including citrulline, lanosterol, and squalene. The increased abundances of Prevotella_1, Ruminococcaceae_UCG.002, and Prevotellaceae_YAB2003 might result in increased fiber digestion and nutrient utilization but nutrient digestion was not measured in the current study. In summary, saponins have the ability to modulate the ruminal microbial community and ruminal metabolites and thus affect the rumen environment. However, the response seems to be dependent on the composition of the basal diet. This study provides a comprehensive overview of the microbial and biochemical changes in the rumen of cattle fed saponins.